Ball milling boosted the activation of peroxymonosulfate by biochar for tetracycline removal. Issue 6 (December 2021) - Zhang, Wei; Yan, Liangguo; Wang, Qiaodi; Li, Xuguang; Guo, Yanxiu; Song, Wen; Li, Yanfei
Abstract: Biochar materials have been commonly applied in advanced oxidation processes, and various strategies were explored to enhance the practical performance of biochar. In this study, ball milling, a simple grinding method, were used to treat biochar, and the ball-milled biochar materials were used to activate peroxymonosulfate (PMS) for tetracycline (TC) removal. It was demonstrated that the ball-milled biochar materials using different ball mass ratios and ball milling time benefited the generation of oxygen-functional groups and defects on the surface, thereby enhanced the catalytic performance of biochar to degrade TC. Besides, the different experimental conditions (initial pH, catalyst dosage, PMS dosage, and TC dosage) and coexisting substances all affected the degradation efficiency of TC. Electron paramagnetic resonance and radicals quenching experiments showed that the radicals attached to the biochar contributed greatly to the degradation of TC, and both free radicals and non-free radicals participated in the TC degradation process. Graphical Abstract: ga1 Highlights: Ball milling is an effective method to improve the catalytic activity of biochar. Ball milling promoted the generation of reactive oxygen species by biochar. C=O group and defective structure via ball milling assisted in PMS decomposition. Radicals (SO4 – and OH) and nonradicals ( 1 O2 ) worked together to degrade TC. Surface-bonded radicals are the main species of reactive oxygen species.